2014
DOI: 10.1001/jamaoto.2013.5842
|View full text |Cite
|
Sign up to set email alerts
|

Adenoidectomy as an Adjuvant to Primary Tympanostomy Tube Placement

Abstract: The current evidence suggests that primary Ad + TT may be superior to TT only in decreasing the risk of r-TT and the risk of RAOM, OME, or otorrhea. Limitations include heterogeneity of the source data, with the predominance of retrospective data as well as studies with older children supporting the superiority of adjuvant adenoidectomy. The practice of Ad + TT may decrease the risk of repeated surgery in children older than 4 years.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
38
0
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(45 citation statements)
references
References 24 publications
4
38
0
3
Order By: Relevance
“…These results are similar to those of most previous studies on this topic, most of them around 40% to 50% [10], [15], [17][19], [35]. If a child requires tube insertion at the age of 2–4 years, he or she are more likely to have tube re-insertions.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…These results are similar to those of most previous studies on this topic, most of them around 40% to 50% [10], [15], [17][19], [35]. If a child requires tube insertion at the age of 2–4 years, he or she are more likely to have tube re-insertions.…”
Section: Discussionsupporting
confidence: 90%
“…Many studies show that adenoidectomy is only beneficial to children of certain age groups. In three studies, Gates et al and Maw showed that adenoidectomy was beneficial in children with OME older than 4 years [11], [12], [14], and one most recent systemic review and metanalysis also concluded that adenoidectomy with primary tube insertion appears to provide a protective effect against repeated surgery in children older than 4 years [35], while Hammaren-Malmi et al demonstrated that adenoidectomy did not reduce OME in children younger than 4 years old [21]. However, Coyte et al found that adenoidectomy was beneficial to children older than 2 years old and that the benefits were more obvious among children older than 3 years old [15].…”
Section: Introductionmentioning
confidence: 99%
“…Similar results evolved from another study [62]. A recent systematic review and meta-analysis [63•] compared TT insertion alone with combined surgery with TT and adenoidectomy. Fifteen studies were included, main outcome measure was repeated surgery with TT and r-TT.…”
Section: Preventionsupporting
confidence: 76%
“…Recurrent infections, including recurring otitis media (ROM) and adenoid hypertrophy (AH), are common indications for adenoidectomy (3). Consequently, acting on these factors could reduce the requirement for surgery.…”
mentioning
confidence: 99%